Prognostic Impact of Memory CD8(+) T Cells on Immunotherapy in Human Cancers: A Systematic Review and Meta-Analysis - Jin, Yao; Tan, Aili; Feng, Jia; Xu, Zexi; Wang, Peiwei; Ruan, Peng; Luo, Ruijun; Weng, Yiming; Peng, Min (Frontiers in Oncology, 2021)
Abstract Objective: The objective of this systematic review and meta-analysis was to determine the prognostic value of memory CD8(+) T cells in cancer patients with immunotherapy. Methods: EMBASE, MEDLINE (PubMed), and Web of Science databases were searched to identify eligible articles published before March 2021. Risk of bias on the study level was assessed using the Cochrane Bias Risk Assessment Tool. The hazard ratios (HRs) and 95% confidence intervals (CIs) of pooled progression-free survival (PFS) and overall survival (OS) were calculated by RevMan 5.4 to evaluate the prognostic impact of memory CD8(+) T cells. Results: In total, 9 studies were included in the final analysis. High levels of memory CD8(+) T cells were significantly correlated with better progression-free survival (PFS) and overall survival (OS) of cancer patients with immunotherapy (PFS, HR 0.64, CI 0.53-0.78; OS, HR 0.58, 95%CI 0.48-0.71 ). What is more noteworthy is that memory CD8(+) T cells can still greatly predict the outcome of immunotherapy in cancer patients with immunotherapy alone after excluding other interfering factors such as chemotherapy, radiotherapy, and targeted therapy (PFS, 0.65, 95%CI 0.48-0.89; OS, HR 0.23, 95% CI 0.13-0.42). Conclusions: Not only the tumor itself, but also the immune status of host should be considered to predict the efficacy of immunotherapy in cancer patients. This study is the first to show the significant prognostic value of memory CD8(+) T cells in immunotherapy of cancer patients through systematic review and meta-analysis. Thus, the detection of memory CD8(+) T cells has a considerable clinical practice value in cancer patients with immunotherapy, memory CD8(+) T cells may act as a promising immunotherapy target.